2020
DOI: 10.1073/pnas.1917922117
|View full text |Cite
|
Sign up to set email alerts
|

Rbm24 controls poly(A) tail length and translation efficiency of crystallin mRNAs in the lens via cytoplasmic polyadenylation

Abstract: Lens transparency is established by abundant accumulation of crystallin proteins and loss of organelles in the fiber cells. It requires an efficient translation of lens messenger RNAs (mRNAs) to overcome the progressively reduced transcriptional activity that results from denucleation. Inappropriate regulation of this process impairs lens differentiation and causes cataract formation. However, the regulatory mechanism promoting protein synthesis from lens-expressed mRNAs remains unclear. Here we show that in z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 57 publications
3
64
0
Order By: Relevance
“…For example, both the N-terminal and C-terminal regions of Rbm24 are required for interaction with Stk38 kinase [ 29 ]. Although the N-terminal region of zebrafish Rbm24a does not directly interact with cytoplasmic polyadenylation element-binding protein 1b (Cpeb1b) and cytoplasmic poly(A)-binding protein 1l (Pabpc1l), its absence decreases the capacity of the C-terminal region to interact with these partners [ 20 ]. Thus, Rbm24 displays biochemical and functional conservation with respect to Rbm38, and its functionality in different cellular processes may be regulated through interaction with specific protein partners.…”
Section: Rbm24 Functional Domainsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, both the N-terminal and C-terminal regions of Rbm24 are required for interaction with Stk38 kinase [ 29 ]. Although the N-terminal region of zebrafish Rbm24a does not directly interact with cytoplasmic polyadenylation element-binding protein 1b (Cpeb1b) and cytoplasmic poly(A)-binding protein 1l (Pabpc1l), its absence decreases the capacity of the C-terminal region to interact with these partners [ 20 ]. Thus, Rbm24 displays biochemical and functional conservation with respect to Rbm38, and its functionality in different cellular processes may be regulated through interaction with specific protein partners.…”
Section: Rbm24 Functional Domainsmentioning
confidence: 99%
“…Loss of Rbm24 severely impairs heart development in zebrafish and mouse embryos [ 14 , 17 , 20 , 33 , 38 ]. Knockdown or knockout of rbm24a in zebrafish is sufficient to cause severe cardiogenic defects [ 14 , 20 , 33 ]. Although rbm24a morphants or mutants have a beating heart, blood is only transported back and forth between the ventricle and atrium.…”
Section: Rbm24 Regulates Muscle Cell Development Through Distinct mentioning
confidence: 99%
See 2 more Smart Citations
“…RBM24 is an RNAbinding protein that contains an RNA-recognition motif (RRM) and an alanine-rich low-complexity region. It has been shown that RBM24 regulates pre-mRNA alternative splicing as well as mRNA stability and translation [24,[29][30][31][32][33][34][35][36][37][38]. RBM24 is a major regulator of muscle-specific alternative splicing, and global Rbm24 inactivation affects cardiac development that eventually leads to embryonic death [24].…”
Section: Neural Plasticitymentioning
confidence: 99%